Port systems and regional hierarchies in Africa in the long term - (:unkn) unknown (My University, 2020)
This chapter looks at an initial approach to the long-term evolution of African port hierarchies. This analysis of port hierarchies is based on throughput volumes (import and export trade) taking into account the mix of cargo, in order to observe the relative position of each port. Secondly, this paper also explores the degree of centrality of seaports through the number of vessel calls thanks to data collected from the Lloyd index. We assume that both indicators are correlated and they gave rise to the self-reinforcement effects which provided stability and robustness for port hierarchies in the long term.
Keywords: African Research